2017
DOI: 10.1111/jvh.12744
|View full text |Cite
|
Sign up to set email alerts
|

Audio‐computer‐assisted survey interview and patient navigation to increase chronic viral hepatitis diagnosis and linkage to care in urban health clinics

Abstract: Intravenous drug use and sexual practices account for 60% of hepatitis C (HCV) and B (HBV) infection. Disclosing these activities can be embarrassing and reduce risk reporting, blood testing and diagnosis. In diagnosed patients, linkage to care remains a challenge. Audio-computer-assisted survey interview (Audio-CASI) was used to guide HCV and HBV infection testing in urban clinics. Risk reporting, blood testing and serology results were compared to historical controls. A patient navigator (PN) followed up blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The definition of linkage to care varies across studies. Studies have defined linkage as confirmatory HCV RNA testing in patients found to have HCV antibodies,1619 referral to specialty clinics among viremic patients,8,2029 or both 3035. Two studies defined linkage to care as receiving HCV RNA testing, referral to specialty care and attending the first appointment with the specialist 36,37.…”
Section: Discussionmentioning
confidence: 99%
“…The definition of linkage to care varies across studies. Studies have defined linkage as confirmatory HCV RNA testing in patients found to have HCV antibodies,1619 referral to specialty clinics among viremic patients,8,2029 or both 3035. Two studies defined linkage to care as receiving HCV RNA testing, referral to specialty care and attending the first appointment with the specialist 36,37.…”
Section: Discussionmentioning
confidence: 99%
“…15 Though several methods have been reported to increase HIV, HCV and HBV risk reporting, additional computers and staffing are required and thus a lesser chance of broad implementation. 16,17 Electronic health record (EHR) systems may present an opportunity to improve screening for chronic illness. Algorithms can be built into EHR systems using combinations of structured data to identify patients at risk for diabetes, heart disease and liver disease.…”
Section: Although the Center For Disease Control And Prevention (Cdc)mentioning
confidence: 99%
“…Lack of knowledge and awareness regarding chronic viral hepatitis is common among physicians and patients, contributing to under‐reporting . Though several methods have been reported to increase HIV, HCV and HBV risk reporting, additional computers and staffing are required and thus a lesser chance of broad implementation …”
Section: Introductionmentioning
confidence: 99%
“…In public health, assessment of the equilibrium of healthcare facilities is focused on multidimensional indicators and categories of elements, usually including one or more of the social, economic, health, and environmental dimensions [22][23][24]. Social and economic assessment studies include social health benefits, financial expenditures for the construction of healthcare facilities, service volume, and hospital class, while health and social environment assessments include the number of facilities in the region, the surrounding environment, land-uses, the health needs of the population, and the experience of accessing healthcare [25][26][27].…”
Section: Introductionmentioning
confidence: 99%